Mental Health of Employed Family Caregivers in Canada: A Gender-Based Analysis on the Role of Workplace Support. (December 2022) - Li, Lun; Lee, Yeonjung; Lai, Daniel W.L.
This study examines the effect of gender differences in mental health outcomes among employed family caregivers, focusing on the role of workplace support in balancing work and caregiving. Guided by the social role theory, this study analyzes nationally representative data from the 2012 Canada General Social Survey, with a sample of 2, 426 participants. Women experience worse mental health outcomes than men when they require employment adjustment to fulfill their caregiving responsibilities. Workplace support could offset the negative effects of employment adjustment on mental health either directly or indirectly through family–work conflict, but gender difference is apparent in terms of the effect of workplace support. In general, women require more supportive workplace than men. Further study of the effects of various types of workplace support on the mental health among women who are employed family caregivers, and on more tailored support, is recommended.